Predictive value of serum procalcitonin level for the diagnosis of bloodstream infections in hematological patients - Qi Sun; Qingsong Lin; Yanxia Lv; Zhiying Tian; Qiushuang Yan; Yaqing Yu; Xue Fu; Hongjing Yao; Fujun Sun; Yonghui Xia; Guoqing Zhu; Sizhou Feng (BMC Infectious Diseases)
Abstract Objectives Procalcitonin (PCT) is a critical diagnostic biomarker for bacterial infections in patients. Numerous studies have shown that PCT have high sensitivity and specificity for diagnosing bloodstream infection. However, the cut-off value of PCT for the diagnosis of bloodstream infections in patients with hematolgic diseases is still unclear and unreliable. Methods We conducted a retrospective study involving 2299 cases with hematological diseases and who had been performed blood culture and PCT test within 24 h. Results For patients with hematological diseases, the serum PCT was slightly elevated in the BSI group. We found that most hematological patients with bloodstream infection were in the stage of severe neutropenia. The main infected strains were Escherichia coli (n = 84, 21%), Klebsiella pneumoniae (n = 61, 15.25%) and Pseudomonas aeruginosa (n = 65, 16.25%), and the increasing trend of PCT level was more obvious in patients infected with Gram-negative bacteria. ROC analysis results showed that the area under the receiver operating characteristic curve for distinguishing bacterial infection from non-bacterial infection was 0.554 (95%CI: 0.522–0.585) with the diagnostic threshold of BSI (PCT > 0.5ng/mL). Conclusions In our study, low PCT levels were found in patients with hematological diseases, and a better cut-off value may be necessary to determine infection in hematology patients.